(untitled) (Al-Farooq Journal of Sciences, 2026)
One of the most significant external parasites afflicting agricultural animals globally, especially in tropical and subtropical areas, is the tick. In addition to directly contributing to financial losses through decreased milk production, weight loss, and skin damage, they also play a significant role in spreading a number of pathogenic agents that endanger the productivity and health of animals. The majority of research on tick prevalence and species distribution in Libya dates back to the colonial and early post-colonial eras, making these studies few and dispersed. With an emphasis on ticks’ biological and ecological traits, their effects on the economy and productivity, and the current understanding of their distribution in Libya, this study attempts to offer a theoretical framework on the prevalence of tick infestation in farm animals in that country. This study highlights the need for updated epidemiological investigations and finds gaps in the existing literature by drawing on secondary sources, such as published articles, reports, and prior surveys. The results indicate that tick infestation is still a major problem for Libyan livestock output, posing a threat to food security and causing large financial losses. In order to lessen the negative effects of ticks on farm animals and promote livestock sustainability in Libya, the study ends by suggesting more applied research, better management techniques, and integrated tick control tactics.